First report of the genus Tricondylomimus Chopard, 1930 (Mantodea, Gonypetidae) from India with a note on its geographical distribution - Ambayathingal P. Kamila; Pavittu M. Sureshan (Journal of Insect Biodiversity and Systematics, 2024)
The genus Tricondylomimus Chopard, 1930 (Mantodea, Gonypetidae) is reported for the first time from India with the species T. coomani Chopard, 1930, based on a female specimen collected from Namdapha National Park, Arunachal Pradesh, India. This species was earlier reported only from Vietnam in the Oriental region. This is the third species of the tribe Iridopterigini (Gonypetidae, Iridopteriginae) that occurred in India. The extension in the distribution of the genus points to the high chances of T. coomani being reported from adjacent countries like Myanmar, Thailand, Laos and Cambodia. The geographical distribution of T. coomani and its resemblance with another group of insects is briefly discussed.